THE IMAGE OF WOMEN FROM THE SUFI PERSPECTIVE OF RABIAH AL-ADAWIYAH - Afifuddin Idrus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the role and contribution of female Sufis in the development of Sufism, which has historically been dominated by male figures. The marginalization of women in Sufi historiography is influenced by strong patriarchal cultural constructs that limit women's space and recognition. While the name of Rabi'ah al-Adawiyah is widely known as a central female figure in Sufism particularly through her concept of mahabbah (divine love) there are other female Sufis such as Sha'wanah, Nafisah, and Fatimah of Nisyapur whose contributions are equally significant but less documented. This paper employs a qualitative-descriptive approach to explore the biographies, spiritual characteristics, and intellectual contributions of these female Sufis. It further analyzes the relevance of Rabi'ah al-Adawiyah’s thoughts and exemplary life in shaping the character of modern Muslim women. The findings show that female Sufis possessed high levels of spirituality, knowledge, and social engagement, and were respected by male scholars of their time. Rabi'ah, in particular, represents an ideal integration of intellectual depth, spiritual devotion, independence, and social responsibility. The study concludes that the values embodied by female Sufis such as asceticism, pursuit of knowledge, social concern, professionalism, and spiritual orientation are highly relevant for modern women. These values can serve as a framework for developing independent, balanced, and spiritually grounded female identities in the contemporary era, without neglecting their roles in family and society. Keywords: Female Sufism; Rabi’ah al-Adawiyah; Mahabbah (divine love); Women’s emancipation; Modern Islamic spirituality